DEIKSIS PERSONA BAHASA INDONESIA DIALEK AMBON [Personal Deixes of Indonesian Leanguage With Ambonese Dialect] - Taufik Salamun (TOTOBUANG, 2017)
Personal deixis of Indonesian language especially in Ambonese dialect are widely use in everyday conversation. This study aimed to describe the forms of personal deixes in Indonesian Leanguage with Ambon Dialect. The research was conducted as a descriptive qualitative study. This type of research is a qualitative descriptive study of objective language phenomena. The data research were oral data obtained from communicative interaction in the Ambon society in the city and its surroundings. The data were collected from people of various ages who used Indonesian language with Ambon dialect. The data were collected using the method of observation with recording and note-taking techniques. The classified data were analysed using the descriptive qualitative method. The results show that the deixes in Indonesian leanguage with Ambon dialect consist of the first singular and plural personal pronoun, second singular and plural pronoun, third singular and plural personal pronoun, and personal pronouns of kinsip lexeme. Deiksis persona bahasa Indonesia dialek ambon banyak digunakan dalam percakapan sehari-hari. Penelitian ini bertujuan mendeskripsikan bentuk-bentuk deiksis persona bahasa Indonesia dialek Ambon. Jenis penelitian ini bersifat deskriptif kualitatif yang mengkaji fenomena kebahasaan yang secara objektif. Data dalam penelitian berupa data lisan yang bersumber dari tindak komunikasi masyarakat kota Ambon dan sekitarnya yang terdiri atas semua rentan usia, yang menggunakan bahasa Indonesia dialek Ambon. Data dikumpulkan menggunakan metode observasi melalui teknik rekam dan catat. Data yang telah diklasifikasi dianalisis secara deskriptif kualitatif. Hasil penelitian menunjukkan bahwa deiksis bahasa Indonesia dialek ambon terdiri atas pronomina persona pertama tunggal dan jamak, pronomina persona kedua tunggal dan jamak, pronomina persona ketiga tunggal dan jamak, dan pronomina persona leksem kekerabatan.